2017
DOI: 10.1111/inm.12359
|View full text |Cite
|
Sign up to set email alerts
|

Towards relational recovery: Nurses’ practices with consumers and families with dependent children in mental health inpatient units

Abstract: Facilitating parent-child and family connections during parental hospitalization provides important opportunities for mental health services to support individual and family recovery. Nurses are often the primary point of contact for families in the inpatient context. They play an integral role in the care provision of consumers and families and in supporting consumers' recovery. The aim of the present qualitative study was to explore nurses' practice with families in inpatient mental health settings in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Farrelly et al 's () review of 13 articles on therapeutic relations with providers and consumers in the mental health community supports this: while providers and consumers agreed on the need for shared trust, respect and collaboration, providers felt what they were to accomplish was unclear and questioned whether or not it was congruent with their roles (Farrelly et al, ). Foster and Isobel () found that nurses in their study were aware of this incongruence and voiced uncertainty in lack of confidence over their abilities, which impacted the recovery‐focused relationship. This may be complicated by an issue addressed earlier: the lack of institutional clarity in many countries on how to actualize broad recovery approaches to care (Baker et al, ).…”
Section: Barriersmentioning
confidence: 99%
“…Farrelly et al 's () review of 13 articles on therapeutic relations with providers and consumers in the mental health community supports this: while providers and consumers agreed on the need for shared trust, respect and collaboration, providers felt what they were to accomplish was unclear and questioned whether or not it was congruent with their roles (Farrelly et al, ). Foster and Isobel () found that nurses in their study were aware of this incongruence and voiced uncertainty in lack of confidence over their abilities, which impacted the recovery‐focused relationship. This may be complicated by an issue addressed earlier: the lack of institutional clarity in many countries on how to actualize broad recovery approaches to care (Baker et al, ).…”
Section: Barriersmentioning
confidence: 99%
“…family, friend, or community) nor how these different relationships might promote or hinder an individual's recovery. While Foster and Isobel () recommend a family‐centred relational recovery approach, they found that mental health nurses lack the confidence to support such practice and require specific training with organizational policy at all levels. Maybery & Reupert () synthesized family‐focused practice with recovery in terms of (1) acknowledging the family role of the client (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…). Due to this, there are mounting calls for more inclusive approaches that consider adults in the context of their family life and recognize child, parent, and family relationships and the needs of parents (Foster & Isobel ; Foster et al . ; Goodyear et al .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates there are service‐related, clinician‐related, and family‐related barriers to provision of mental health family‐focused care. There is a substantial body of evidence that, while nurses and other clinicians recognize the importance of addressing consumers’ needs as a parent and family member, they can struggle with a lack of confidence, lack of role clarity, and lack of clinical skills and knowledge to engage readily with parent/consumers and their children about mental illness (Foster & Isobel ; Goodyear et al . ; Maybery et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation